The Convergence of Nanotechnology, Biotechnology and Cancer Medicine in the Fourth Industrial Revolution - Steven Mufamadi; Zamanzima Mazibuko (The Thinker)
Medical technologies of the fourth industrial revolution (Industry 4.0), such as nanotechnology, biotechnology, artificial  intelligence (AI), 3D printing and advanced materials are already transforming medical technology and the pharmaceutical industry by offering accurate diagnoses, targeting therapies with fewer side effects, and providing better medical imaging and personalised medicine.